Sign Languages in Britain and Ireland - Leeson, Lorraine (Cambridge University Press, 2024)
Deaf people are typically multilingual and use multimodal resources, i.e. sign, writing and speech, for communication in their everyday lives (Quinto-Pozos & Adam 2013). This is due to the fact that only 5% of all deaf children are born into deaf families and thus acquire a sign language once they start attending a Deaf school and get into contact with Deaf culture (Woll et al. 2001, Woll & Ladd 2003). The same holds true for the approximately 5,000 members of the Irish Deaf community, consisting of Deaf, hard of hearing people, and their family and friends (Matthews 1996). Schooling and prevalent educational policies like oralism, stipulating the use of spoken language as medium of instruction up until the second half of the 20th century, have (had) a crucial impact not only on the use of Irish Sign Language (ISL), but also on its structure (cf. Mohr 2012). ISL, genetically descending from French Sign Language, is Ireland’s third native language and was legally acknowledged in the Irish Sign Language Bill passed by the Oireachtas in 2017 (The Irish Times 2017). Due to language contact, Irish English is visible in different contact phenomena in ISL, which are the focus of this chapter. The abundance of language contact with ambient spoken languages results in a plethora of contact phenomena, such as borrowings of spoken words (e.g. Mohr 2012), code-blending of sign and speech (e.g. Emmorey et al. 2005) or fingerspellings and initialized signs, formed with the handshape of the first letter of the sign’s meaning in the ambient spoken language (e.g. Quinto-Pozos 2007). The chapter focuses on mouthings, fingerspellings and initialized signs, which have all been shown to be closely linked to gender variation in ISL, brought about by separate schooling and different educational practices in Irish deaf schools until the end of the 20th century (Matthews 1996, Le Master 1990, Leeson & Grehan 2004, Mohr 2012). Mouthings, for instance, have been shown to be a more frequent feature of female signing (Mohr 2012), in opposition to initialized signs, which are more frequent among men (Le Master 1990). This is closely linked to the separate male and female varieties of ISL that existed until the 1990s. The analysis presented in the chapter is based on the Signs of Ireland Corpus, a multimodal video corpus of ISL (Leeson 2008), consisting of data from 40 signers between 18 and 65 years of age, collected at 5 different locations in Ireland. The corpus has been extensively annotated over several years using the ELAN software tool developed by the Max Planck Institute for Psycholinguistics in Nijmegen. Altogether, the chapter not only outlines the intricacies of language contact across the oral-aural and visual-gestural modalities in Ireland, but also depicts the dynamics of (educational) policies and social differences of language use in linguistic minority communities.
Language in Britain and Ireland
PUBLISHED
Cambridge
Keywords: Irish Sign Language; Gendered generational signing; Irish Sign Language; Identities in Transformation; Inclusive Society; Making Ireland; British Sign Language; Irish Sign Language